1992
DOI: 10.1111/j.1600-0404.1992.tb05097.x
|View full text |Cite
|
Sign up to set email alerts
|

Daytime sleepiness: a risk factor in community life

Abstract: The prevalence of daytime sleepiness and background factors associated with it were investigated in a study carried out at the UKK Institute. The inquiry took the form of a questionnaire mailed to 1600 people of middle age. Daytime sleepiness was found to be associated with disturbed night sleep. Women were more tired than men, but men slept more frequently during the day. Those suffering from tiredness complained of poor health more than other respondents. Traffic accidents and other mishaps attributable to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 4 publications
4
34
2
3
Order By: Relevance
“…A number of previous studies have examined the relationship between excessive daytime sleepiness and various types of sleep problems and underlying diseases. 5,[7][8][9][10][11][12] A British study reported that symptoms of insomnia such as difficulty initiating sleep and difficulty maintaining sleep, breathing pauses or leg pain during sleep, and depressive disorder were associated with excessive daytime sleepiness. 9 In Japan, Liu et al reported that excessive daytime sleepiness was associated with short sleep duration, insomnia symptoms, subjective sleep insufficiency and use of sleep-enhancing medication.…”
Section: Methodsmentioning
confidence: 99%
“…A number of previous studies have examined the relationship between excessive daytime sleepiness and various types of sleep problems and underlying diseases. 5,[7][8][9][10][11][12] A British study reported that symptoms of insomnia such as difficulty initiating sleep and difficulty maintaining sleep, breathing pauses or leg pain during sleep, and depressive disorder were associated with excessive daytime sleepiness. 9 In Japan, Liu et al reported that excessive daytime sleepiness was associated with short sleep duration, insomnia symptoms, subjective sleep insufficiency and use of sleep-enhancing medication.…”
Section: Methodsmentioning
confidence: 99%
“…More than one-fourth of these respondents (27%) said they have driven drowsy to or from work at least a few days a month, 12 percent drove drowsy a few days a week, and four percent said they drove drowsy every day or almost every day 9) . Similarly, according to data from Australia, England, Finland, and other nations-all of which have more consistent crash reporting procedures than the U.S.-drowsy driving represents at least 10-20 percent of all crashes [13][14][15][16][17][18][19] . This data shows that we have only begun to scratch the surface in determining the real extent of the problem of driver fatigue and has led some to term drowsy driving "the silent killer".…”
Section: The Scope Of the Drowsy Driving Problemmentioning
confidence: 99%
“…It has been reported that EDS affects 0.5-14% of the population, (1)(2)(3)(4) seriously interfering with professional activities, as well as with family and social relationships, and reducing cognitive performance, thereby increasing the risk of accidents in the workplace and traffic accidents. (5)(6)(7)(8) It has been demonstrated that individuals who are sleep-deprived, due to limitations in either the quantity or quality of sleep, often are unable to respond rapidly to external stimuli and have greater difficulty in concentrating, which impairs their ability to perform certain activities, including driving a vehicle.…”
Section: Introductionmentioning
confidence: 99%